Responses to structural violence: The everyday ways in which queer and trans migrants with precarious status respond to and resist the Canadian immigration regime - Edward Ou Jin Lee (International Journal of Child, Youth & Family Studies, 2019)
This article examines how the Canadian immigration regime socially organizes the everyday lives of queer and trans migrants with precarious status. Drawing from key findings from an institutional ethnographic study, this article maps out the disjuncture between the actual experiences of queer and trans migrants with precarious status and the ideological and textual production of precarious status by the Canadian state. Making explicit this disjuncture reveals how the Canadian immigration regime enacts structural violence upon queer and trans migrants. This article also engages with the response-based approach to violence in order to understand how queer and trans migrants actively respond to this violence. In doing so, this article highlights the ways in which queer and trans migrants respond and resist the structural violence integral to the Canadian state’s production of precarious status.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; identités LGBTQIA2+; immigration; pol4212; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; transféminisme; violences